HUBUNGAN ANTARA KOMUNIKASI INTERPERSONAL GURU DAN MOTIVASI KERJA DENGAN KINERJA GURU PADA MAN BARANGIN SAWAH LUNTO - Oky Loly Wenny (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Relationship Between Interpersonal Communication Teacher and Motivation Work Teacher With Teacher Performance in Madrasah Aliyah Negeri (MAN) Barangin Sawah Lunto. The purpose of this research is to investigate the contribution of teachers interpersonal communication (X1) and teachers working motivation (X2) with teachers performance of Madrasah Aliyah Sawahlunto City (Y).The instrument which is used for questionaires, consist of 35 items for variable Y, 30 items for variable X1, and 26 items for variable X2. Testing of analysis requirement was performed by Liliefors. The result of analysis shows the following result: (1) the contribution of interpersonal communication to teacher’s performance is 30,5%, (2) the contribution of motivation to teacher’s performance is 10,5%, (3) the contribution of interpersonal communication an motivation variable simultaneously to the teacher’s performance is 31,5%. Conclusion of this research was interpersonal communication and motivation simultaneously has significant contribution toward teacher’s performance.Kata Kunci: komunikasi interpersonal, motivas kerja, dan kinerja guru